Pengaruh Differensiasi Produk dan Kualitas Produk terhadap Keputusan Pembelian Mukena Bordir Khas Bukittinggi - Susanti Putri Utami; Thamrin Thamrin (Universitas Negeri Padang, 2021)
Abstract : The purpose of this study was to determine the effect of product differentiation and product quality on purchasing decisions for the typical Bukittinggi embroidery mukena among the people of Bukittinggi City. This research is a causative research. The population in this study were the native people of the City of Bukittinggi. The number of research samples was 100 people and were selected using purposive sampling technique. The data used are primary data obtained through distributing questionnaires to the native people of Bukittinggi with predetermined criteria. The analytical method used is multiple regression analysis using SPSS 22. The results showed that (1) product differentiation and product quality have a positive and significant effect on purchasing decisions, (2) product differentiation has a positive and significant effect on purchasing decisions (3) product quality has a positive and significant influence on purchasing decisions. Keywords: product differentiation, product quality and purchasing decision